How do fathers and mothers allocate their leisure time? Patterns and inequalities across 13 European countries - Anna Martinez Mendiola (Demographic Research)
BACKGROUND: Spending time on leisure is widely recognised as a significant source of enjoyable psychological experiences in daily life. However, cross-national studies on time use and gender inequalities frequently overlook the study of leisure. OBJECTIVE: This study has two principal objectives. First, it presents estimates of leisure time among parents, providing detailed insights into how fathers and mothers allocate their leisure time. Second, it explores patterns and variations in leisure time allocation and gender inequalities across European countries. METHODS: This study uses data from the second round of the Harmonised European Time Use Survey (HETUS) to analyse leisure time among parents (n = 76,867) across 13 European countries. This research focuses on parents because of their limited opportunities for leisure. The study examines seven dimensions that consider the type of activity and the presence of other family members. RESULTS: Analogous patterns of leisure time allocation and gender inequalities exist across Europe. Fathers and mothers spend the majority of their leisure time on sedentary activities, either alone or with other adults. However, mothers spend less leisure time overall, particularly in sedentary activities, and more leisure time with their children. CONTRIBUTION: This note provides new insights into how European parents spend their leisure time, highlighting cross-country patterns in time allocation and gender inequalities via time-use data from 13 European countries. It also emphasises the importance of considering different dimensions of leisure time for a more comprehensive understanding.